DEEP LEARNING-BASED TEXTURE SYNTHESIS FOR SCULPTURAL REALISM - Thakur, Shyamsing; Om Prakash; Saxena, Kumud; Singla, Abhishek; Potteti, Sumalatha; Bhoite, Sonali Prashant (ShodhKosh: Journal of Visual and Performing Arts, 2025)
In this paper, a multi-scale deep learning model that takes into account geometry to produce high-fidelity texture is proposed to condition on digital sculptures. The use of traditional 2D texture generation methods on complex 3D surfaces can be characterized by the presence of seam artifacts, distortions and disappearance of microstructural details, which makes them inappropriate in sculptural realism. The model is optimized on a multi-objective loss comprising of adversarial, perceptual and style components and patch-level and geometry-aware components and refined using differentiable rendering to match real lighting behaviour. It has been shown by experimental results of significantly better early results compared to classical techniques, StyleGAN-based baselines and diffusion based generators, lower perceptual error (LPIPS), seam discontinuity (SCI, PBD) and multi-view consistency. Human perceptual research supports that the suggested approach prevails in almost 70% of the pair-wise tests with references to greater material authenticity and geometric consistency. The results illustrate the usefulness of viewing texture synthesis as a 2D-3D joint learning task and define the introduced system as a potential source of digital sculpting, heritage modeling, virtual production, and high-end assets all of which require material realist.